2016
DOI: 10.1515/cipms-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Modern kinetic spectrophotometric procedure for estimation of furosemide drug as bulk form and in pharmaceuticals preparations

Abstract: A simple, rapid, sensitive, inexpensive and easy to perform kinetic spectrophotometric procedure for the investigation of trace quantities of the drug, furosemide (FRO), as bulk and in the pharmaceutical preparations, has been improved upon. The enhanced method was depended on the fashioning of the Schiff ‘s base by the reaction of the aldehyde group present in the 5-sulfo salicylaldehyde reagent, and the primary amino group present in furosemide. The latter acts as a ligand for the formation of an intense col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For the repeatability analysis, six specimens of tablet formulations were analyzed. Calculation of standard deviation and RSD percentage [32,33].…”
Section: Validation Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the repeatability analysis, six specimens of tablet formulations were analyzed. Calculation of standard deviation and RSD percentage [32,33].…”
Section: Validation Of the Proposed Methodsmentioning
confidence: 99%
“…Separate orders of attachment of reagents were investigated and it was observed that the sequence of introduction of materials by combining drug and acid hydrochloride with ceric ammonium nitrate after 25min methyl blue solution that provided the strongest absorption after 5min and was used in certain ensuing tests [32].…”
Section: Order Of Addition Influencementioning
confidence: 99%
“…Each of the studied excipients was given independently by ten-times concentrations more than of MCP prepared by the self-approach in the calibration curve. 1 ml of 500 ppm MCP and 1 ml of every excipients were connected for the study of interferences [21]. Dilution to the sign of volumetric flask 25 ml grade of impedance was made.…”
Section: Interferencesmentioning
confidence: 99%
“…3 (2). [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] J. Islamic Pharm., an open access journal ISSN : 2527-6123 administration. Urinary excretion is the major elimination pathway for ceftriaxone sodium.…”
Section: Introductionmentioning
confidence: 99%